PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP RETURN SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL MEDIASI - IRIANING - SUPARLINAH (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2020)
Abstract Good corporate governance (GCG) is implemented by companies in order to achieve financial performance, one of which is measured by company profitability. Investors pay more attention to this profitability in making price decisions and the expected returns. This study aims to analyze the effect of the GCG structure, which includes institutional ownership, managerial ownership, the proportion of independent commissioners and the proportion of the audit committee on stock returns with profitability as the mediating variable. Purposive sampling was carried out to select stocks that were included in the trade, service and investment sectors listed in 2018. Data from 38 companies were analyzed by regression analysis. From the research it is concluded that profitability mediates the effect of good corporate governance on stock returns. There is no proven direct effect of GCG on stock returns. As an implication; Investors are generally interested in examining the company's profitability, in this case return on assets. Profitability (ROA) is also a reflection of good corporate governance implemented by the company. From several GCG indicators, the proportion of independent commissioners has an effect on company profitability. Indeed, the board of commissioners is responsible for ensuring the implementation of good corporate governance and control to achieve optimal company performance.